(untitled) (Diseminaciones, 2022)
In David Miklos’ tale “Hágalo usted mismo”, fragmentation manifests in two levels. In the textual level, is in the division in vignettes, in the constant presence of meaningful iterations and in the figure of the character through its reflection in a doll to assemble. In another level, fracture reaches the author’s figure since his image gleams in the title and in other elements dispersed in the text. This paper outlines a brief history of the edition of this peculiar tale and gives important details about its location. The analysis is based in Myrna Solotorevsky’s proposal about the aesthetics of fragmentation and it recovers some considerations about specular tale and autofiction in order to demonstrate that this text is a specular-tale, which marks reflect the essence of El abrazo de Cthulhu.